PENGEMBANGAN IDEAL SOLUTION SYSTEM VERSI 2.0 DENGAN MENERAPKAN MODEL PROTOTYPING - Rani Purbaningtyas; Didit Rahmat Hartadi (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Applications Ideal Solution System version 1.0 is an application developed independently since 2014 to solve various problems are multiple criteria as well as having the characteristics of the benefit factor and cost factor. In manufacturing, this application implementing TOPSIS method as basic algorithms used program. But in its implementation, there is still a shortage or revision of the user. Note the revision of the user obtained during the implementation phase is the basis for the developers to develop applications. Therefore, developers are trying to develop the Ideal Solution System version 2.0, which was developed with reference to the model prototyping. Ideal Prototype Solution System version 2.0 has been tested and found viable easy use testing because it is easy and convenient for the user so operate the application.